INNOVATIVE METHODS FOR ASSESSING AND MONITORING PSYCHOPHYSIOLOGICAL CONDITIONS OF PERSONS WITH INTELLECTUAL DISABILITIES - Korotkova A.K.; Korotkov K.G.; Banayan A.A.; Baryaev A.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the use of the gas discharge visualization method in identifying the features of the psychophysiological state of people with intellectual disabilities involved in sports. Methods and structure of the study. The method of gas discharge visualization (GDV) is based on recording the emission of electrons and photons from the skin under the action of high voltage voltage pulses. The emerging glow in the ultraviolet range of the spectrum is recorded by special cameras. When analyzing the psychophysiological state of a person, the glow is recorded from the fingers of a person. The analysis is based on the principles of Traditional Chinese Medicine (TCM), which make it possible to establish a connection between the fingers and individual organs and systems of a person. The study took place during the year, at training events. For this study, data were selected (shooting from 10 fingers) of 200 athletes from 17 to 25 years old. Results and conclusions. The data obtained indicate the presence of statistically significant differences in the parameters of the GDV method for the group of persons with intellectual disabilities (ID) from the group of healthy athletes. These data and their temporal dynamics can provide the doctor and coach with additional information about the current state of the observed athletes. At the same time, they cannot serve as a diagnostic sign for identifying pathological conditions.